Formulating Natural Disaster Insurance Scheme for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia - Setijawan, Edi; Sutiyono, Guntur; Wicaksono, Gandhi Cahyo; Ardiyanti, Historya; Christi, Petra (The International Journal of Financial Systems, 2023)
The existence of disaster insurance in Indonesia is particularly important for disaster-prone areas. In recent years, only 2.96% of 64 million MSMEs have disaster insurance. This is because the existing disaster insurance scheme has not fully met the expectations of MSMEs regarding its premium value, its claims mechanism and MSMEs financial capability. This research seeks to explore the factors that influence MSMEs to own disaster insurance, by using quantitative analysis of Panel Fixed Effects Model as the first model and Probit Models as the second and third models as well as qualitative analysis. The result will be utilized to formulate the appropriate disaster insurance product which optimize insurance features based on MSMEs’ demand, encourage regulatory support and improve government funding capacity. Indonesia is currently facing approximately IDR19.75 trillion (USD1.4 billion) financing gap to cover the loss caused by disasters hence, there is also a need to create a high- level financing scheme to cover the gap.